Discovery of benzimidazole‐based Leishmania mexicana cysteine protease CPB2.8ΔCTE inhibitors as potential therapeutics for leishmaniasis. (31st May 2018) - De Luca, Laura; Ferro, Stefania; Buemi, Maria Rosa; Monforte, Anna‐Maria; Gitto, Rosaria; Schirmeister, Tanja; Maes, Louis; Rescifina, Antonio; Micale, Nicola
Abstract : Chemotherapy is currently the only effective approach to treat all forms of leishmaniasis. However, its effectiveness is severely limited due to high toxicity, long treatment length, drug resistance, or inadequate mode of administration. As a consequence, there is a need to identify new molecular scaffolds and targets as potential therapeutics for the treatment of this disease. We report a small series of 1, 2‐substituted‐1 H ‐benzo[ d ]imidazole derivatives (9a–d ) showing affinity in the submicromolar range ( K i  = 0.15–0.69 μM) toward Leishmania mexicana CPB2.8ΔCTE, one of the more promising targets for antileishmanial drug design. The compounds confirmed activity in vitro against intracellular amastigotes of Leishmania infantum with the best result being obtained with derivative9d (IC50  = 6.8 μM), although with some degree of cytotoxicity (CC50  = 8.0 μM on PMM and CC50  = 32.0 μM on MCR‐5). In silico molecular docking studies and ADME‐Tox properties prediction were performed to validate the hypothesis of the interaction with the intended target and to assess the drug‐likeness of these derivatives. Abstract : A small series of 1, 2‐substituted‐1 H ‐benzo[ d ]imidazole derivatives showed affinity in the submicromolar range ( K i  = 0.15–0.69 µM) towards a promising target (i.e. Leishmania mexicana CPB2.8ΔCTE) for anti‐ Leishmania drug design, as well as micromolar activity in vitro against the intracellular form of the parasite. In silico molecular docking studies and ADME‐Tox properties prediction validated the hypothesis of the interaction with the intended target and assessed the drug‐likeness of these derivatives.